OVERVIEW OF HANDLING FEVER IN TODDLERS AT HOME IN MERANGKAI VILLAGE IN 2025 - Putri Wulandini S; Sukarni; Anggraini Fitrianingsih (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Toddlerhood is a period in the growth and development of children. Fever or febrile is a condition where the body temperature becomes higher than usual, and this is a symptom of the disease. Fever treatment can be done through a pharmacological, non-pharmacological approach, or a combination of both. The purpose of this study was to determine the description of fever treatment in toddlers by parents at home in the village of Merangkai in 2025. This study is a qualitative study with a phenomenological design. Sampling was carried out using Snowball Sampling where the sampling technique used for research on things that are quite sensitive and require a high level of privacy from the respondents. The number of data that met the inclusion criteria was 9 samples. This study used a structured interview method as data collection for research. An interview is a conversation between parents and directly between respondents and researchers verbally to obtain information. The results of the study with a sample of nine (9) respondents regarding the description of fever management in toddlers by parents at home in Merangkai village, it can be concluded that the treatment of fever given is with warm water compresses. Warm water compresses have proven effective in treating fever in toddlers which is marked by a decrease in body temperature.